Kesesuaian Nisbah Simpanan Berjangka Terhadap Hukum Islam Di BMT Bina Ummat Sejahtera Gondangrejo - Samudra, Dhimas Raja; Romdhoni, Abdul Haris; Sumadi, Sumadi (ITB AAS INDONESIA Surakarta, 2024)
This research was conducted to determine the determination of the profit sharing ratio for term savings at BMT Bina Ummat Sejahtera Gondangrejo. The profits obtained from this product are shared based on a predetermined agreement. With profits divided proportionally between shahibul maal and mudharib. Term savings product as a means for BMT Bina Ummat Sejahtera to increase income. This type of research is field research using a qualitative approach. Data collection in this research was through documentation, observation and interviews. Data analysis techniques use editing, classification, analysis and conclusions. Meanwhile, to test the validity of the data using triangulation. Based on the results of research conducted by the author, it can be concluded that the determination of the profit sharing ratio for term savings products at BMT Bina Ummat Sejahtera is in accordance with the mudharabah profit sharing method, namely profits become joint property and joint ownership rights.